Efektivitas WhatsApp Group dalam Meningkatkan Minat Belajar Siswa pada Pembelajaran PAI di SMKN 2 Kota Cirebon - Ahmad Fathuroji; Akhmad Affandi; Siti Maryam Munjiat (Al-Fikr: Jurnal Pendidikan Islam, 2021)
The use of learning media must continue as a consequence of the distance between educators and students. This is done to establish a distance learning network in future pandemic Covid-19. This study aims to determine how the use of WhatsApp Group, student learning interest using WhatsApp Group, and supporting and inhibiting factors in increasing student learning interest using WhatsApp Group, especially in PAI subjects at SMKN 2 Cirebon City. To get the data, researchers used qualitative research methods. The informant is obtained from subjects who are determined using purposive and snowballing. The technique of collecting data through observation, interviews, and documentation. The process of data analysis including data collection, data reduction, data presentation, and verification or conclusion. The results show that WhatsApp Group media can assist educators in carrying out their duties, help overcome students' passive attitudes, and help present information and instructions. Students interested in learning can be seen from the interest, involvement, sense of excitement, and attention during the lesson. Supporting factors include the enthusiasm and consistency of educators, facilities, and encouragement for interaction, the ability to use media, and communication problems that can be resolved on the spot. The obstacles include inadequate infrastructure, requiring students to study independently, no face-to-face activities, and difficulties in evaluation.